Exploring the traditional ritual of Jaran Kepang Papat: context, heritage, and significance - Rr. Paramitha Dyah Fitriasari; Maharani Hares Kaeksi (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2023)
This paper investigates the traditional ritual of Jaran Kepang Papat, examining its contextual significance, cultural heritage, and the profound role it plays within the Indonesian cultural landscape. Jaran Kepang Papat is a unique and captivating ritual deeply rooted in Javanese culture. Through an interdisciplinary exploration encompassing anthropology, history, and cultural studies, this research unravels the intricate web of meaning and symbolism embedded in the ritual. The method employed in this research is descriptive qualitative. Researchers initiated the data collection process through in-depth interviews with ritual participants, community leaders, and cultural experts knowledgeable about Jaran Kepang Papat. These interviews provide comprehensive insight into the history, meaning, and significance of this ritual. Additionally, researchers engaged in participatory observation during the implementation of the ritual to gain a direct understanding of how it is carried out and experienced by the participants. The paper concludes by emphasizing the importance of understanding and safeguarding Jaran Kepang Papat as a valuable cultural treasure, advocating for its continued recognition and appreciation within the broader cultural discourse. This exploration serves as a testament to the enduring significance of traditional rituals in our globalized society, offering valuable insights into the preservation and appreciation of cultural heritage.